Synthesis of novel psoralen analogues derived from 7-hydroxy-4-methylcoumarin - Francisco, Carla Santana (2012)
Fundação para a Ciência e a Tecnologia (FCT) FEDER (European Fund for Regional Development)-COMPETE-QREN-EU FCOMP-01-0124-FEDER-022716